KAPITALISME GLOBAL DAN MEDIA DAKWAH - Widoyo, Agus Fatuh (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2025)
Global capitalism is a world reality. Essentially, is a manifestation of the phenomenon of cultural improvism. Capitalism is not only concerned with production techniques, but is a totality that includes the fields of politics, economics, social relations, etc. The need for Islamic broadcasting to mass media is non-negotiable and has become a necessity in the modern era. Global capitalism in development can be a threat to Islamic broadcasting in radio mass media. It causes broadcast radio stations to experience distorts, from what was originally idealism oriented to profit oriented. Muslims who are engaged in the media, especially radio media, must think of anticipatory steps to face the symptoms of global capitalism, for the sake of the continuity of Islamic da'wah.